Toward sustainable construction: Comprehensive utilization of coal gangue in building materials - Lei Zhang; Dehui Zhu; Afshin Marani; Moncef L. Nehdi; Ling Wang; Guofan Yang; Junfei Zhang (Case Studies in Construction Materials)
Coal gangue (CG), as a major solid waste byproduct of the coal industry, has attracted widespread attention due to its potential in construction materials. This review systematically evaluates the activation mechanisms and engineering performance of CG, exploring the impact of various activation methods such as thermal, mechanical, chemical, microwave, and synergistic activation on its hydration potential. The findings suggest that activated CG can significantly enhance the cementitious performance of cement-based materials, reduce cement consumption, and contribute to sustainable construction practices. Thermal activation enhances CG reactivity by removing combustible components and transforming mineral phases, while mechanical activation increases the specific surface area through fine milling. Chemical activation, using alkaline or acidic activators, promotes the formation of hydration products by depolymerizing silica-aluminate networks, and microwave activation rapidly enhances reactivity by converting electromagnetic energy into thermal energy. When used as a supplementary cementitious material, activated CG improves durability, but may also affect workability and mechanical properties. When used as an aggregate, CG’s high water absorption and low elastic modulus can lead to increased shrinkage and reduced freeze-thaw resistance, requiring strict control of the substitution ratio. Future research should focus on optimizing activation methods to enhance CG’s reactivity and performance, while addressing challenges related to its high water absorption and variable mineral composition. Additionally, a life cycle assessment of CG utilization in construction materials should be conducted to comprehensively evaluate its environmental impact.